Functions of agents in regional entrepreneurial ecosystem in the conditions of digital transformations - V. A. Androsova; V. A. Yakimova (Вестник университета, 2023)
The article discusses the role and functions of agents in the context of entrepreneurial ecosystem development. Theoretical aspects of agent role have been reflected and main functions that agents perform in entrepreneurial ecosystem of region highlighted. The article highlights importance of agents as key players that ensure functioning of ecosystem. The research methodology is based on the methods of assessing fulfillment of agent functions by means of ranking analysis in the context of the proposed indicators. A comparative assessment of agents’ functioning in entrepreneurial ecosystems of regions has been carried out in the Republic of Tatarstan, the Chelyabinsk Region, the Tomsk Region, the Trans-Baikal Territory, and the Amur Region. The analysis of regional ecosystems in comparison with the reference region (Tatarstan) made it possible to identify dysfunctions in the work of agents in underdeveloped regions. It has been revealed that functions of supporting start-ups and research and innovation functions are not fully implemented in some regions.